17β-Estradiol Attenuates LPS-Induced Macrophage Inflammation In Vitro and Sepsis-Induced Vascular Inflammation In Vivo by Upregulating miR-29a-5p Expression. (10th June 2021) - Zhang, Man-li; Chen, Hui; Yang, Zhan; Zhang, Man-na; Wang, Xia; Zhao, Kun; Li, Xuan; Xiu, Nan; Tong, Fei; Wang, Ya-xuan
Abstract : Excessive release of cytokines such as IL-1 β and other inflammatory mediators synthesized and secreted by macrophages is the fundamental link of uncontrolled inflammatory response in sepsis. 17 β -Estradiol (E2) plays anti-inflammatory and vascular protective effects by regulating leukocyte infiltration and the expression of chemokines or cytokines induced by injury. However, the role of E2 in the inflammatory response of macrophages in sepsis and its mechanism are still not fully understood. In the present study, we show that E2 alleviates vascular inflammation in sepsis mice induced by cecal ligation puncture (CLP). E2 significantly decreases RAW 264.7 cell inflammation response by downregulating the expression of NLRP3. Furthermore, we found that miR-29a-5p was significantly downregulated in LPS-treated macrophages. Treating RAW 264.7 cells with E2 markedly upregulated the miR-29a-5p expression level. More importantly, we demonstrated that miR-29a-5p repressed NLRP3 expression by directly targeting its 3 ′ -UTR. Loss- and gain-of-function experiments revealed that transfection of the miR-29a-5p mimic abrogates LPS-induced macrophage inflammation. Moreover, depletion of miR-29a-5p by its inhibitor largely promotes LPS-induced macrophage inflammation. In summary, miR-29a-5p upregulation induced by E2 alleviated RAW 264.7 cell inflammation response by aggravating miR-29a-5p repression of NLRP3 expression. E2 exerts significant anti-inflammatory efficacy in macrophages by regulating the miR-29a-5p/NLRP3 axis. Targeting miR-29a-5p may be a novel therapeutic strategy to suppress sepsis-induced vascular inflammation.